Applicability of an oligonucleotide probe in radioisotope 32P-based dot blot hybridization for detection of hepatitis C virus in large sample numbers: a preliminary study (Medical Journal of Indonesia, 2012)
Background: This study aimed to design and analyze the applicability of an oligonucleotide probe in radioisotope 32P-based dot blot hybridization for detection of hepatitis C virus. Methods: Forty-six of plasma samples were used. The plasma was extracted to obtain viral RNA genome as template for RT-PCR and the amplicon was used for nested PCR. Twenty-four HCV genomes were retrieved from GeneBank DNA sequence and alignment was performed by Bio Edit Software version 7.0.9.0. An oligonucleotide probe was designed based on a highly conserved region that is located on internal sequence between two primers used for nested PCR. Blast analysis on GeneBank was performed to obtain homology of the oligonucleotide for HCV. The oligonucleotide was then labeled with 32P and dot blot hybridization was applied for nested PCR products. DNA Sequencing was performed to confirm the amplicon and dot blot hybridization results. Results: Blast analysis showed high homology (100%) for HCV. Nested PCR resulted in three patterns of DNA fragments representing HCV genotypes 1, 2, and 3, respectively. The primers used in nested PCR were not specific and resulted in DNA fragments difficult to be interpreted. Dot blot hybridization using the designed oligonucleotide showed high intensity dots. All nested PCR fragments showed the dot blot positive. The dot blot results were in accordance with DNA sequencing that confirmed three patterns of DNA fragments as different HCV genotypes. Conclusion: The oligonucleotide showed excellent bioinformatically criteria. 32P-based dot blot hybridization yielded high intensity dots and was easier to be interpreted than nested PCR assay. (Med J Indones. 2012;21:71-6)